Taxonomy of the subgenus Pseudocypus Mulsant & Rey (Coleoptera: Staphylinidae: Staphylinini) and eight new species from China - He, Liang; Zhou, Hong-Zhang (Zootaxa, 2017)
Eight new species of the subgenus Pseudocypus Mulsant & Rey, 1876 of the genus Ocypus Leach, 1819 (Coleoptera, Staphylinidae, Staphylinini) are described from China: O. (Pseudocypus) pileaticulminis sp. nov., O. (Pseudocypus) denticulminis sp. nov., O. (Pseudocypus) anguliculminis sp. nov., O. (Pseudocypus) digiticulminis sp. nov., O. (Pseudocypus) alticulminis sp. nov., O. (Pseudocypus) fusciculminis sp. nov., O. (Pseudocypus) nigriculminis sp. nov. and O. (Pseudocypus) recticulminis sp. nov. Line drawings and color illustrations of adult structures and genitalia are given for all new species and the following species recorded in China: O. (Pseudocypus) aenescens Eppelsheim, 1889, O. (Pseudocypus) ballio Smetana, 2007, O. (Pseudocypus) calamis Smetana, 2007, O. (Pseudocypus) densissimus (Bernhauer, 1933), O. (Pseudocypus) dolon Smetana, 2007, O. (Pseudocypus) graeseri Eppelsheim, 1887, O. (Pseudocypus) hecato Smetana, 2007, O. (Pseudocypus) inexspectatus Eppelsheim, 1887 (new record in China), O. (Pseudocypus) menander Smetana, 2007, O. (Pseudocypus) neocles Smetana, 2007, O. (Pseudocypus) orodes Smetana, 2007, O. (Pseudocypus) pelias Smetana, 2007, O. (Pseudocypus) puer (Smetana, 2005a), O. (Pseudocypus) picipennis (Fabricius, 1793), O. (Pseudocypus) rhinton Smetana, 2007, and O. (Pseudocypus) semenowi Reitter, 1887. A key to Chinese species of the subgenus Pseudocypus Mulsant & Rey, 1876 is also provided in the text.